2022
DOI: 10.1001/jamaophthalmol.2022.2914
|View full text |Cite
|
Sign up to set email alerts
|

Severe Familial Exudative Vitreoretinopathy, Congenital Hearing Loss, and Developmental Delay in a Child With Biallelic Variants in FZD4

Abstract: This case series investigates if variants in the FZD4 gene are associated with familial exudative vitreoretinopathy (FEVR) with extraocular features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…They suggested that the variants resulted in dramatic loss of Norrin-FZD4 signaling and therefore cause extraocular features. 9 The clinical presentation of the affected individual presented here is isolated, severe FEVR in childhood. This is in line with the findings of Khan et al 8 who describe recessive FEVR without extraocular features.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…They suggested that the variants resulted in dramatic loss of Norrin-FZD4 signaling and therefore cause extraocular features. 9 The clinical presentation of the affected individual presented here is isolated, severe FEVR in childhood. This is in line with the findings of Khan et al 8 who describe recessive FEVR without extraocular features.…”
Section: Discussionmentioning
confidence: 86%
“…8 Recently, biallelic FZD4-variants were described as a possible cause of FEVR with extraocular features including hearing loss and developmental delay, because of complete knock-down of the Norrin/Frizzled-4 pathway. 9 This also appears to be the case for hemizygous NDP-variants causing Norrie disease. 10 In addition, heterozygous variants in LRP5 are mainly linked to either FEVR or increased bone density, while biallelic LoF variants cause a syndromic form (OMIM*603506).…”
mentioning
confidence: 85%
“…Two cases in our study were progressed very badly, may be due to FZD4 variant. 6 FFA was not helpful to diagnose and treat. Treatment in these cases did not show any response.…”
Section: Discussionmentioning
confidence: 94%
“…[ 32 ] reported that most eyes of 13 probands with two disease-causing variants had stage 4 (38.46%) or stage 5 (26.92%) disease. A case series detected a heterozygous biallelic variant in FZD4 leading to hearing deficits and developmental delays [ 19 ]. In LRP5 variants, a higher incidence of severe phenotype was observed in patients with biallelic variants compared to those with monoallelic variants [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Catenin beta 1 ( CTNNB1 ) is also an uncommon cause of microcephaly [ 18 ]. Frizzled-4 ( FZD4 ) variants can result in hearing deficits and developmental delays [ 19 ]. Current research indicates that only around 40–50% of cases of FEVR harbour identifiable genetic variants [ 20–22 ], while the relationship between the genotype and clinical manifestations is complex, which are responsible for the challenges in early clinical diagnosis and effective treatment.…”
Section: Introductionmentioning
confidence: 99%